Polanyi's Economic Embeddedness, Countermovement, and Republican Political Economy - Escandell, Bru Laín (Ethics, Politics & Society, 2018)
The aim of this article is to contend that Karl Polanyi's work bears significant coincidences with the republican tradition of thought. The first of them is one of a methodological or epistemological kind, and it consists of the use of a very
Keywords: countermovement; embeddedness; political economy; political economy and history; political philosophy; republicanism